Structure and Composition of Nanometer-Sized Nitrides in a Creep-Resistant Cast Austenitic Alloy - Evans, Neal D.; Maziasz, Philip J.; Shingledecker, John P.; Pollard, Michael J. (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2010)
The microstructure of a new and improved high-temperature creep-resistant cast austenitic alloy, CF8C-Plus, was characterized after creep-rupture testing at 1023 K (750 °C) and 100 MPa. Microstructures were investigated by detailed scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy (EDS). Principal component analysis of EDS spectrum images was used to examine the complex precipitate morphology. Thermodynamic modeling was performed to predict equilibrium phases in this alloy as well as the compositions of these phases at relevant temperatures. The improved high-temperature creep strength of CF8C-Plus over its predecessor CF8C is suggested to be due to the modified microstructure and phase stability in the alloy, including the absence of δ -ferrite in the as-cast condition and the development of a stable, slow-growing precipitation hardening nitride phase—the tetragonal Z-phase—which has not been observed before in cast austenitic stainless steels.